Implementasi Tasawuf Syekh Abdul Qadir al-Jailani dalam Majelis Manakib Al Barokah Ponorogo - Moh Ashif Fuadi; Rustam Ibrahim (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
One of the most popular sufi figures in the world is Shekh Abdul Qadir al-Jailani. The significant number of followers is due to his tremendous knowledge in various fields. In the reciting activities of Shekh Abdul Qadir al-Jailani’s manakib explained his life history and grandeurs. In some of his works, he explains the teachings of sufism so that manakib practitioners can live up more to this. Also, he states to what extent the values of sufism are applied. The purpose of writing this article is to find out the sufism teachings of al-Jailani referring to his work and to know the implementation of his Sufism teachings in the Al Barokah Ponorogo manakib assembly with their routine agenda on the 11th night of the Hijri month. This study employs library sources combined with field observation on the assembly’s activities. The results show that the sufism teachings of al-Jailani in the book al-Ghunyah Li Thalib Thariq al-Haq are mujahadah, tawakkal, good morals, gratitude, patience, ridha, honesty, which in its implementation through the explanation and example of kiai have been practiced by the congregation of Al Barokah manakib and manifested in social behaviors. Keywords: al-Jailani, jamaah, manakib assembly, tasawuf. Salah satu tokoh sufi yang terpopuler di dunia adalah Syekh Abdul Qadir al-Jailani. Banyaknya penggemar tokoh sufi tersebut disebabkan oleh ketinggian ilmunya di berbagai bidang. Dalam kegiatan pembacaan kitab manakib Syekh Abdul Qadir al-Jailani, dijelaskan sejarah hidup berikut karomah-karomahnya. Dalam beberapa karyanya ia menjelaskan ajaran-ajaran tasawuf sehingga bisa semakin dihayati oleh pengamal manakib serta sejauh mana nilai-nilai ajaran tasawuf diterapkan oleh pengamalnya. Tujuan penulisan artikel ini untuk mengetahui ajaran-ajaran tasawuf al-Jailani merujuk pada karyanya dan mengetahui implementasi ajaran tasawufnya di majelis manakib Al Barokah Ponorogo yang diselenggarakan rutin tiap tanggal 11 bulan Hijriyah. Kajian ini menggunakan sumber pustaka dipadukan dengan pengamatan lapangan pada kegiatan majelis tersebut. Hasil penelitian menunjukkan bahwa ajaran tasawuf al-Jailani dalam kitab al-Ghunyah Li Thalib Thariq al-Haq adalah mujahadah, tawakkal, akhlak baik, syukur, sabar, ridha, jujur yang dalam implemetasinya melalui penjelasan dan keteladanan kiai sudah dipraktekkan oleh jamaah Al Barokah dan terwujud dalam perilaku sosial. Kata kunci: al-Jailani, jamaah, majelis manakib, tasawuf.